Quality by design of yogurt product using taguchi multi responses method - Ali Parkhan; Muhammad Ridwan Andi Purnomo (Universitas Ahmad Dahlan, 2020)
Quality of yogurt could be determined based on its flavor and texture which could be tested using an organoleptic test. The quality objective of the yogurt flavor and texture is larger the better. As one of the intermediate products that could be processed to become various other products, the demand for yogurt is continuously increasing in Indonesia. Along with the increase in demand, the demand for quality of yogurt has also increased. In this study, experiments have been conducted to improve the quality of a yogurt product. The experiments were designed based on the Taguchi method with Multi Responses Signal to Noise (MRSN) that involves 7 factors consists of 6 controllable factors and 1 uncontrollable factor. Every factor has 2 levels of an experiment. The 6 controllable factors are heating temperature, heating duration, number of yogurt seeds, incubation temperature, incubation duration, number of sugars, while the uncontrollable factor is the weather condition. Result of the experiments showed when weight for flavor and texture is 0.437 and 0.563 respectively, the levels of the optimum factors are 950C for milk heating temperature, 20 minutes for the duration of milk heating process, 75 ml of yogurt seeds, 450C of the temperature of incubation, 6 hours of incubation duration and 12.5 grams of sugar weight. Based on the organoleptic test that conducted by a group of experienced testers, the new optimum factors combination could improve the yogurt’s quality in term of flavor and quality up to 16.24% and 11.37% respectively. It could be concluded that the proposed method could improve the quality of yogurt-based on preferences from the experienced testers that have been expressed by the weight of every quality response.